The Impact of Information Technology on the Audit Process: Auditors' Perspectives - Santoso, Bima (Golden Ratio of Auditing Research, 2021)
This qualitative study explores auditors' perceptions of ethical responsibility in the auditing profession, aiming to elucidate the complexities of ethical decision-making. Through semi-structured interviews, seasoned auditors provided insights into their experiences, attitudes, and challenges related to ethical conduct. The research employed a phenomenological approach to understand the essence of auditors' lived experiences concerning ethical responsibility. Data collection involved semi-structured interviews with practicing auditors, allowing for in-depth exploration of their perspectives. A purposive sampling strategy was adopted to select participants with relevant knowledge and experience in IT-enabled auditing practices. Thematic analysis was utilized to analyze interview transcripts and identify key themes and patterns. The findings revealed that auditors perceive ethical responsibility as fundamental to their professional identity, emphasizing the importance of upholding ethical standards, maintaining independence, and exercising professional judgment. Challenges in ethical decision-making included pressure from clients, financial incentives, time constraints, and conflicting demands from stakeholders. Organizational culture emerged as a critical factor influencing auditors' ethical behavior, highlighting the importance of ethical leadership, firm policies, and peer behavior. The study underscores the need for comprehensive ethical training, organizational support, and regulatory oversight to promote ethical conduct among auditors and uphold the credibility of the auditing profession.